Analysis of the Effect of Pricing Policy, Investment Decision Making, and Service Quality on Financial Performance in Financial Services Companies in West Java - Kaligis, Ervina; Judijanto, Loso; Irdhayanti, Efa (West Science Social and Humanities Studies, 2024)
This research investigates the intricate interplay between pricing policy, investment decision-making, service quality, and financial performance within financial services companies in West Java. Employing a quantitative research design, data was collected from 152 companies through a structured survey and analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The measurement model confirmed the reliability and validity of the chosen indicators, while the structural model unveiled significant relationships. Results indicate that strategic pricing policies, informed investment decisions, and high service quality positively influence financial performance. The synergistic effect of integrating these elements contributes to a comprehensive understanding of the strategic dynamics in West Java's financial services sector.